Evolutionary policy - Jeroen C.J.M. van den Bergh; Giorgos Kallis (Max Planck Institute of Economics, 2009)
We explore the idea of public policy from the perspective of evolutionary thinking. This involves paying attention to concepts like diversity, population, selection, innovation, coevolution, group selection, path-dependence and lock-in. We critically discuss the notion of evolutionary progress. The relevance of evolutionary dynamics is illustrated for policy and political change, technical change, sustainability transitions and regulation of consumer behaviour. A lack of attention for the development of evolutionary policy criteria and goals is identified and alternative choices are critically evaluated. Finally, evolutionary policy advice is compared with policy advice coming from neoclassical economics, public choice theory and theories of resilience and adaptive management. We argue that evolutionary thinking offers a distinct and useful perspective on public policy design and change.
Keywords: 330; Adaptive management; coevolution; escaping lock-in; evolutionary politics; evolutionary progress; innovation policy; optimal diversity; resilience; social-technical transition